2015
DOI: 10.1002/mds.26348
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology and Cellular Pathogenesis of Spinocerebellar Ataxia Type 12

Abstract: Objective SCA12 is a progressive autosomal-dominant disorder, caused by a CAG/CTG repeat expansion in PPP2R2B on chromosome 5q32, and characterized by tremor, gait ataxia, hyperreflexia, dysmetria, abnormal eye movements, anxiety, depression, and sometimes cognitive impairment. Neuroimaging has demonstrated cerebellar and cortical atrophy. We now present the neuropathology of the first autopsied SCA12 brain and utilize cell models to characterize potential mechanisms of SCA12 neurodegeneration. Methods A fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…A similar scenario can be anticipated in SCA12 where the CAG repeat expansion in a non-coding (untranslated) region of PPP2R2B. In SCA12 it has been shown that the length of the CAG repeats alters the expression of the PPP2R2B (Lin et al, 2010;O'Hearn et al, 2015). Overexpression of CAG repeat containing isoform of a noncoding RNA in SCA12 is reminiscent of the expression pattern observed in FXTAS (Hagerman, 2013) and may exert cytotoxic effects through various mechanisms such as RAN translation, antisense and poly-serine mediated pathophysiology (Zu et al, 2011;Nalavade et al, 2013).…”
Section: Recapitulation Of Gene Expression Signatures Of Other Neurodsupporting
confidence: 54%
See 3 more Smart Citations
“…A similar scenario can be anticipated in SCA12 where the CAG repeat expansion in a non-coding (untranslated) region of PPP2R2B. In SCA12 it has been shown that the length of the CAG repeats alters the expression of the PPP2R2B (Lin et al, 2010;O'Hearn et al, 2015). Overexpression of CAG repeat containing isoform of a noncoding RNA in SCA12 is reminiscent of the expression pattern observed in FXTAS (Hagerman, 2013) and may exert cytotoxic effects through various mechanisms such as RAN translation, antisense and poly-serine mediated pathophysiology (Zu et al, 2011;Nalavade et al, 2013).…”
Section: Recapitulation Of Gene Expression Signatures Of Other Neurodsupporting
confidence: 54%
“…The generated neurons displayed characteristics of a pan-neuronal lineage. We did not expect morphological differences in these SCA12 neurons at early stages as like other neurodegenerative disease SCA12 produces a late onset phenotype and even neuropathological studies have not shown any morphological differences in the disease affected brain areas except for neuronal loss and gliotic changes (O'Hearn et al, 2015).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The two dominant transcripts (ENST00000394411.8 and ENST00000394409.7, Figure , red dotted frame) only contain 9 coding exons. PPP2R2B has well‐characterized expression in brain tissues . Therefore, we compared its expression profile in sarcoma with normal brain tissues.…”
Section: Resultsmentioning
confidence: 99%